Constitutionality of Attempt to Commit Suicide- Unlocking The Controversy (Medico Legal Update, 2020)
A person is born free but he does not have this freedom to choose his death. Suicide is a deliberate act of killing of oneself. Suicide as such is not a crime but when an attempt is taken it can be considered as one under Section 309 of Indian Penal Code. The debate round the corner is whether attempt to commit suicide should be punished or not. A person was aware of the outcome of committing suicide, still knowingly takes an attempt. Suicide as a problem is the mixture of social, psychological, philosophical, moral, ethical and legal reasons behind it. An act of suicide requires grave awareness because there is nothing an ordinary prudent man fears more than his death, and that fear in the huge majority of cases, is as logical as it is inevitable. This paper has drawn the attention towards the ongoing debate of retaining or deleting Section 309 by testing its validity on the ground of Article 21 of the constitution of India which provides right to life as a fundamental right.